INTERCONNECTIVITY AND DIFFERENCES OF THE (INFORMATION) PRIVACY RIGHT AND PERSONAL DATA PROTECTION RIGHT N THE EUROPEAN UNION - Pedic, Zana (Review of European and Comparative Law, 2017)
Right to (information) privacy and right to personal data protection have many common contact points. However, the very act of developing data protection, as a younger right into the sui generis right shows that these two rights are not the same and that there are differences between them, huge enough to make them separate legal rights. The main trigger for noticing their different nature, purpose and background and for development of the data protection into the separate right was the revolution in the information technology solutions. This IT progress, for the first time, enabled massive and relatively cheap operations with the personal data and brought not only concern about the security of the personal data, but also unbelievable business possibilities. It was the turning point for the codification of the data protection right which started from 1970ies, aiming to create separate rules and legislation which will understand the importance of not only of protecting personal data but of their regulated and lawful usage. Despite all what was said, there is still certain confusion regarding these two rights, mainly because in the initial phase of the massive usage of the new IT solutions, when the data protection legislation still wasn’t developed, information privacy right served as the only legal protection of the data protection right and the relationship between these two rights is complex even today and deserves to be further researched